2019
DOI: 10.4238/gmr18379
|View full text |Cite
|
Sign up to set email alerts
|

Research Article <i>Bradyrhizobium</i> spp. as attenuators of water deficit stress in runner peanut genotypes based on physiological and gene expression responses

Abstract: The peanut plant has high plasticity and great adaptability to adverse conditions, including drought. To mitigate the negative effects of drought on legumes, nitrogen-fixing microorganisms have been investigated in some plant species, such as soybeans and beans. We analyzed the role Bradyrhizobium strains in peanut genotypes subjected to water deficit by means of plant growth, physiological and gene expression analysis. The research was conducted under greenhouse conditions with the runner peanut genotypes (IA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, pant001 was the strain that provided the highest mean among the inoculated treatments ( Figure 4 d). In an experiment with peanut genotypes treated with bacterial strains and under water deficit, minimal differences were observed in relation to water restriction [ 41 ]. Despite the plants showing reductions in root growth, the bacterial strains were efficient in promoting growth and water deficit attenuation, emphasizing the importance of using inoculants to mitigate the effects of water deficit [ 12 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, pant001 was the strain that provided the highest mean among the inoculated treatments ( Figure 4 d). In an experiment with peanut genotypes treated with bacterial strains and under water deficit, minimal differences were observed in relation to water restriction [ 41 ]. Despite the plants showing reductions in root growth, the bacterial strains were efficient in promoting growth and water deficit attenuation, emphasizing the importance of using inoculants to mitigate the effects of water deficit [ 12 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed that the application of plant growth-promoting bacteria (PGPB), like to the genera Bacillus spp. and Bradyrhizobium spp., can be used as a strategy to mitigate water stress ( Brito et al., 2019 ; Lastochkina et al., 2019 ). The interaction between plants and microorganisms can also enhance the plant’s tolerance to water deficit, as already assessed in crops such as maize ( Kavamura et al., 2013 ; Santos et al., 2020 ), sorghum ( Santana et al., 2020 ), wheat ( Gontia-Mishra et al., 2016 ), foxtail millet ( Niu et al., 2018 ), tomato ( Gowtham et al., 2020 ), and more recently in sesame ( Lima et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Peanut (Arachis hypogaea L.) can efficiently associate with rhizobia lineages, but is more efficient with the Bradyrhizobium genus (Valetti et al 2016, Barbosa et al 2018, Brito et al 2019. Crop yield can be maximized by using inoculants containing competent strains, favoring the crop management by small producers (Sizenando et al 2016, Valetti et al 2016.…”
Section: Introductionmentioning
confidence: 99%